FSSR lecturer acknowledged at International Art Exhibition / Mahizan Hijaz Mohammad - Mohammad, Mahizan Hijaz (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
Fine Arts Lecturer from the Art and Design Faculty (FSSR), Mr. Mohammad Fadly Sabran won the honourable mention award for his artistic participation of video and light artwork in Artopolitan Festival of International Art Exhibition 2019.